Nb microalloyed steel with good high-temperature corrosion resistance as well as stacking-rotating-gradient cooling hot working method and application of Nb microalloyed steel
By using the "stack-rotation-gradient cooling" hot working method of Nb microalloyed steel, the grains are refined and the microstructure is made uniform, which solves the corrosion resistance problem of steel anode plates in high-temperature corrosive environments, and achieves improved high-temperature corrosion resistance and cost control.
Patent Information
- Application Number
- CN202511374162.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-25
- Publication Date
- 2025-12-26
AI Technical Summary
Existing steel anode plates have poor corrosion resistance in high-temperature corrosive environments, and their uneven structure leads to stress concentration, affecting the service life and purity of rare earth production. Furthermore, existing corrosion-resistant materials are expensive or may affect the purity of rare earth.
By employing Nb microalloyed steel and its "stack-rotation-gradient cooling" hot working method, and by controlling the mass ratio of Nb to C, combined with multi-pass hot compression and gradient cooling processes, the grains are refined and the microstructure is homogenized, forming NbC precipitates that pin grain boundaries and improving high-temperature corrosion resistance.
This technology improves the high-temperature corrosion resistance of Nb microalloyed steel, reduces the grain size to less than 30μm, enhances the uniformity of the microstructure, extends the service life of components such as the anode pressure plate of rare earth electrolysis furnace, and reduces costs.
Smart Images

Figure CN121204533A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of metal hot working, in particular to a Nb microalloyed steel with good high-temperature corrosion resistance and a "stacking-rotating-gradient cooling" hot working method and application thereof. BACKGROUND
[0002] The mainstream rare earth preparation process at home and abroad is the molten salt electrolysis method. The conductive part of the graphite anode, the anode pressing plate, is connected to the preparation link. It faces the harsh service environment of high temperature above 800 DEG C, liquid NdF3-LiF erosion and strong magnetic field, and the control of its corrosion products directly affects the purity of rare earth. Some enterprises try to use Ni-based alloy, stainless steel and other corrosion-resistant materials to improve the service life of the device, but such materials are difficult to meet the economic requirements of industrial production due to high cost, and will also introduce more alloy elements to affect the purity of rare earth. At present, most of the rare earth production enterprises use cast low-carbon steel anode pressing plate to reduce the influence of C element on the purity of rare earth products. Although the low-carbon steel anode pressing plate is low in cost, it has the defects of poor corrosion resistance and more corrosion products. At present, most of the rare earth production enterprises use cast low-carbon steel anode pressing plate. Such devices have the problems of short service life and more corrosion products accumulated in the electrolytic cell. The currently used steel anode pressing plate is difficult to meet the service requirements in harsh working conditions such as high temperature corrosion, which restricts the further development and application of high-purity rare earth preparation.
[0003] At present, the key performance indicators of the anode pressing plate for high-temperature corrosion resistance are the alloy composition, grain size and organizational uniformity of the steel material. Coarse grains and uneven grain size are the two main reasons for the poor high-temperature corrosion resistance of the steel anode pressing plate. First, coarse grains reduce the number of grain boundaries per unit area, and grain boundaries are usually more resistant to corrosion (because they are easy to form passivation film or segregate corrosion-resistant elements), and the reduction of grain boundaries will reduce the overall corrosion resistance of the material. Second, the defects of cast structure lead to stress concentration or defects, and the uneven microstructure in the service process also causes stress concentration and defects. The uneven defects of the steel material due to uneven structure restrict the application and development of the steel device in the high-temperature corrosion environment. As the material of the anode pressing plate of the rare earth electrolytic furnace, the current steel device cannot meet the performance requirements of the rare earth production service.
[0004] Therefore, how to improve the high-temperature corrosion resistance of the steel material and consider the economic cost of its use has become a technical problem to be solved in the field. SUMMARY
[0005] The purpose of the present application is to provide a Nb microalloyed steel with good high-temperature corrosion resistance and a "stacking-rotating-gradient cooling" hot working method and application thereof to solve the above technical problems.
[0006] In order to achieve the above application purpose, the present application provides the following technical solutions:
[0007] The application provides a Nb micro-alloy steel with good high-temperature corrosion resistance, comprising the following chemical components in percentage by mass:
[0008] C 0.15-0.25%, Si 0.2-0.3%, Mn 0.5-0.6%, Ni 0.02-0.03%, Cr 0.015-0.03%, S≤0.0025%, P≤0.02%, Nb≤0.1% and the balance of Fe.
[0009] Further, the mass ratio of C and Nb is 2.5-12.5.
[0010] The application also provides a "stack-rotation-gradient cooling" hot working method of the Nb micro-alloy steel with good high-temperature corrosion resistance, comprising the following steps:
[0011] 1) sequentially adding corresponding raw materials of each component and niobium-iron alloy in the process of ingot smelting to obtain the Nb micro-alloy steel ingot;
[0012] 2) heating and holding the Nb micro-alloy steel ingot, then cooling to the first-pass hot compression temperature to perform the first-pass hot compression, and then immediately water quenching; the ingot after water quenching is mechanically processed into "strip-shaped" samples with the same size;
[0013] 3) heating and holding the Nb micro-alloy steel sample obtained in step 2), then cooling to the second-pass hot compression temperature, after holding, rotating 60° clockwise along the axial direction of the first-pass hot compression, then taking "1 to N strips" of "strip-shaped" samples with the same cross-sectional size, after "end face alignment and stacking assembly", applying axial compression to perform the second-pass hot compression; wherein N≤100;
[0014] 4) taking out the Nb micro-alloy steel sample obtained in step 3) after unloading, cooling to the third-pass hot compression temperature, after holding, rotating 60° clockwise along the axial direction of the second-pass hot compression to perform the third-pass hot compression, and then water quenching, thereby obtaining the Nb micro-alloy steel with good high-temperature corrosion resistance.
[0015] Further, the temperature of the ingot smelting is 1350-1580°C.
[0016] Further, in step 2), the heating temperature is 1200-1300°C, and the holding time is 150-200s.
[0017] The cooling rate is 8-12°C / min, and the first-pass hot compression temperature is 1100-1200°C.
[0018] Furthermore, in step 3), the Nb microalloyed steel ingot is heated to 1250°C and held for 3 minutes;
[0019] The second hot compression temperature is 1000–1100℃, the cooling rate is 8–12℃ / min, and the holding time is 100–150s.
[0020] Furthermore, in step 4), the temperature of the third hot compression is 900–1000°C, the cooling rate is 8–12°C / min, and the holding time is 100–150s.
[0021] Furthermore, the reduction rates of the first, second, and third hot compression passes are independently 15-30%, the total deformation rate of the hot compression is ≥60%, and the strain rate of the hot compression is 1s for each pass. -1 The engineering strain is 0.2.
[0022] This invention also provides an application of Nb microalloyed steel with good high-temperature corrosion resistance in the structural metal materials of anode pressure plates, stirring rods, and molten salt heating furnaces in rare earth electrolysis furnaces.
[0023] The beneficial effects of this invention are:
[0024] This invention reduces the average grain size of Nb-containing steel after hot working by adding Nb, making it more difficult for dislocations to cut through or bypass the small precipitates. Combined with a gradient cooling hot working process, this refines the grain size and improves the uniformity of the microstructure, thereby enhancing the high-temperature corrosion resistance of the steel. Furthermore, by controlling the Nb to C mass ratio, this invention can further improve the uniformity of the microstructure. The addition of Nb ensures that the average grain size of the Nb microalloyed steel is mainly concentrated within 30 μm, further improving the high-temperature corrosion resistance of the alloy. The results of the embodiments show that the minimum average grain size of the Nb microalloyed steel provided by this invention is 23.10 μm, and the fine, uniform grains of the Nb microalloyed steel exhibit uniform surface morphology after corrosion and good high-temperature corrosion resistance. Attached Figure Description
[0025] Figure 1 The present invention presents the original as-cast microstructure of Nb microalloyed low-carbon steel;
[0026] Figure 2 The stress-strain curve of Nb microalloyed low carbon steel under hot compression deformation proposed in this invention.
[0027] Figure 3 This invention proposes a microstructure for Nb microalloyed low-carbon steel subjected to three-stage gradient cooling hot compression.
[0028] Figure 4The original austenite grain diagram of the Nb micro-alloyed low-carbon steel three-pass gradient cooling hot compression is proposed for the application;
[0029] Figure 5 The surface morphology diagram of the Nb micro-alloyed low-carbon steel corroded for 50h under high-temperature molten salt conditions is proposed for the application.
[0030] Figure 6 The corrosion product determination of the Nb micro-alloyed low-carbon steel after being corroded for 50h under high-temperature molten salt conditions is proposed for the application.
[0031] Figure 7 The original as-cast microstructure of the 0wt% Nb low-carbon steel is proposed for the application;
[0032] Figure 8 The stress-strain curve of the 0wt% Nb low-carbon steel hot compression deformation is proposed for the application;
[0033] Figure 9 The microstructure of the 0wt% Nb low-carbon steel three-pass gradient cooling hot compression is proposed for the application;
[0034] Figure 10 The original austenite grain diagram of the 0wt% Nb low-carbon steel three-pass gradient cooling hot compression is proposed for the application;
[0035] Figure 11 The surface morphology diagram of the 0wt% Nb low-carbon steel corroded for 50h under high-temperature molten salt conditions is proposed for the application.
[0036] Figure 12 The corrosion product determination of the 0wt% Nb low-carbon steel after being corroded for 50h under high-temperature molten salt conditions is proposed for the application.
[0037] Figure 13 The original as-cast microstructure of the 0.12wt% Nb low-carbon steel is proposed for the application;
[0038] Figure 14 The stress-strain curve of the 0.12wt% Nb low-carbon steel hot compression deformation is proposed for the application;
[0039] Figure 15 The microstructure of the 0.12wt% Nb low-carbon steel three-pass gradient cooling hot compression is proposed for the application;
[0040] Figure 16 The original austenite grain diagram of the 0.12wt% Nb low-carbon steel three-pass gradient cooling hot compression is proposed for the application;
[0041] Figure 17 The surface morphology diagram of the 0.12wt% Nb low-carbon steel corroded for 50h under high-temperature molten salt conditions is proposed for the application.
[0042] Figure 18 The corrosion product of the 0.12wt% Nb low-carbon steel proposed in the application is determined after corrosion for 50h under high-temperature molten salt conditions.
[0043] Figure 19 The Nb micro-alloy steel gradient cooling thermal deformation process flow chart proposed in the application is shown in the figure.
[0044] Figure 20 The original austenite grain diagram of the low-carbon steel of Comparative Example 1 is shown in the figure.
[0045] Figure 21 The surface morphology diagram of the low-carbon steel of Comparative Example 1 corroded for 50h under high-temperature molten salt conditions is shown in the figure.
[0046] Figure 22 The corrosion product of the low-carbon steel of Comparative Example 1 is determined after corrosion for 50h under high-temperature molten salt conditions. DETAILED DESCRIPTION
[0047] The application provides a Nb micro-alloy steel with good high-temperature corrosion resistance, which comprises the following chemical components in mass percentage:
[0048] C 0.15-0.25%, Si 0.2-0.3%, Mn 0.5-0.6%, Ni 0.02-0.03%, Cr 0.015-0.03%, S≤0.0025%, P≤0.02%, Nb≤0.1% and the balance of Fe.
[0049] In the application, C is preferably 0.2-0.25% and further preferably 0.2-0.22% in mass percentage.
[0050] In the application, Si is preferably 0.25-0.28% and further preferably 0.26-0.27% in mass percentage.
[0051] In the application, Mn is preferably 0.55-0.58% and further preferably 0.56-0.57% in mass percentage.
[0052] In the application, Ni is preferably 0.023-0.028% and further preferably 0.024-0.026% in mass percentage.
[0053] In the application, Cr is preferably 0.02-0.028% and further preferably 0.025-0.026% in mass percentage.
[0054] In the application, S is preferably 0.002-0.0023% in mass percentage.
[0055] In the present application, P is preferably 0.013-0.015% by mass.
[0056] In the present application, Nb is preferably 0.02-0.06% by mass, and further preferably 0.05-0.06% by mass.
[0057] In the present application, the mass ratio of C to Nb is 2.5-12.5, preferably 5-10, and further preferably 6-9. This ratio can ensure that a sufficient amount of NbC precipitates is formed to effectively pin the grain boundaries, while avoiding excessive consumption of solid-solution carbon by Nb, which would affect the performance of the matrix. The content of Mn is 0.5-0.6%, which, in cooperation with the NbC precipitates, can improve the high-temperature corrosion resistance of the material, and Mn can also stabilize the austenite structure and enhance the high-temperature stability.
[0058] The present application also provides a "stacking-rotation-gradient cooling" hot working method for Nb microalloyed steel with good high-temperature corrosion resistance, comprising the following steps:
[0059] 1) sequentially adding corresponding raw materials of each component and niobium-iron alloy during the ingot smelting process to obtain a Nb microalloyed steel ingot;
[0060] 2) heating and holding the Nb microalloyed steel ingot, then cooling to the first-pass hot compression temperature for first-pass hot compression, and immediately water quenching after the hot compression; the ingot after water quenching is mechanically processed into "strip-shaped" samples with the same size;
[0061] 3) heating and holding the Nb microalloyed steel sample obtained in step 2), then cooling to the second-pass hot compression temperature, and after holding, rotating 60° clockwise along the axial direction of the first-pass hot compression, and then taking "1 to N strips" of "strip-shaped" samples with the same cross-sectional size, aligning the end faces, stacking and assembling, and then applying axial compression for second-pass hot compression; wherein N≤100;
[0062] 4) taking out the Nb microalloyed steel sample obtained in step 3) after unloading, cooling to the third-pass hot compression temperature, and after holding, rotating 60° clockwise along the axial direction of the second-pass hot compression for third-pass hot compression, and then water quenching to obtain the Nb microalloyed steel with good high-temperature corrosion resistance.
[0063] In the present application, the temperature for the ingot smelting is 1350-1580℃, preferably 1400-1550℃, and further preferably 1450-1500℃.
[0064] In the present application, in step 2), the heating temperature is 1200-1300℃, and preferably 1250℃; and the holding time is 150-200s, and preferably 180s.
[0065] In the application, the rate of cooling in step 2) is 8-12 ℃ / min, preferably 10 ℃ / min; the first-pass hot compression temperature is 1100-1200 ℃, preferably 1150 ℃.
[0066] In the application, in step 3), the Nb micro-alloyed steel ingot is heated to 1250 ℃ and kept for 3 min.
[0067] The second-pass hot compression temperature is 1000-1100 ℃, preferably 1050 ℃; the rate of cooling is 8-12 ℃ / min, preferably 10 ℃ / min; the holding time is 100-150 s, preferably 120 s.
[0068] In the application, in step 4), the third-pass hot compression temperature is 900-1000 ℃, preferably 950 ℃; the rate of cooling is 8-12 ℃ / min, preferably 10 ℃ / min; the holding time is 100-150 s, preferably 120 s.
[0069] In the application, the reduction rate of the first-pass hot compression, the second-pass hot compression and the third-pass hot compression is independently 15-30%, preferably 18-25%, further preferably 20-24%; the total deformation rate of hot compression is ≥60%, and the strain rate of hot compression is all 1 s -1 , the engineering strain is 0.2.
[0070] In the application, after each-pass hot compression, the temperature is lowered to the next-pass deformation temperature to repeat the above process until the target value of engineering strain is reached, and then water quenching is performed immediately to retain the high-temperature structure, and then the performance of the ingot is studied by sampling.
[0071] In the application, by using a hot compression simulator, the ingot sample is subjected to gradient cooling hot deformation hot working, and the obtained Nb micro-alloyed steel has fine and uniform grain distribution, mainly concentrated below 30 μm, and the average grain size is about 23 μm, and the high-temperature corrosion resistance is good.
[0072] In the application, the sampling mode of the Nb micro-alloyed steel, the Nb-free low-carbon steel and the high-Nb low-carbon steel is to prepare a cylindrical sample with a diameter of Φ10 and a height of 15 mm by using wire cutting, then to polish the end face of the sample by using a metallographic sandpaper (240#, 400#, 800#, 1000#) to eliminate the surface defects left by wire cutting processing, and then to remove the cutting oil stains remaining on the sample surface by using an ultrasonic cleaning equipment with anhydrous ethanol as a solvent.
[0073] The Nb micro-alloyed steel provided by the application has reasonable chemical component design, simple and controllable preparation process, excellent product performance and is convenient for large-scale industrial application.
[0074] The application further provides application of the Nb microalloyed steel with good high-temperature corrosion resistance and uniform microstructure in a rare earth electrolytic furnace anode pressing plate, a stirring rod and a molten salt heating furnace structural material.
[0075] The technical solutions provided by the application are described in detail below in combination with examples, but they should not be understood as limiting the protection scope of the application.
[0076] Example 1
[0077] 1) The steel ingot is obtained by smelting according to the raw material ratio shown in Table 1, and the smelting temperature is 1500℃.
[0078] Table 1 Chemical composition of the Nb microalloyed low-carbon steel (mass fraction, %)
[0079] C Si Mn S P Ni Cr Nb Fe 0.241 0.273 0.561 0.0022 0.014 0.024 0.023 0.058 Bal.
[0080] 2) The Nb microalloyed steel ingot is obtained by sequentially adding the raw materials corresponding to each component and the niobium-iron alloy during the steel ingot smelting process;
[0081] 3) The Nb microalloyed low-carbon steel is processed into a cylindrical sample with a diameter of Φ10mm and a length of 15mm, and then the influence of hot working on the microstructure and properties is studied.
[0082] 4) The Nb microalloyed steel ingot is heated to 1250℃ and kept for 180s, then cooled to 1150℃ at a rate of 10℃ / min, kept for 120s, and then the first pass hot compression sample is carried out at a strain rate of 1s -1 -1, and then immediately water quenched; after the water quenching is completed, the ingot is mechanically processed into a "strip block" sample with the same size; after the compression, it is cooled to 1050℃ at the same rate, kept for 120s, and then the third pass hot compression is carried out along the axial direction of the first pass hot compression after the sample is rotated clockwise by 60° around the shaft by using a clamp; 50 "strip block" samples with the same cross-sectional size are taken, and then the axial compression is applied after the "end face alignment and stacking assembly"; the second pass hot compression is carried out; after the sample is unloaded and taken out, it is cooled to 950℃ at the same rate, kept for 120s, and then the third pass hot compression is carried out along the axial direction of the second pass hot compression after the sample is rotated clockwise by 60°; until the target engineering strain value is reached, and then immediately water quenched to retain the high-temperature microstructure.
[0083] 5) Corrosion experiment uses PrNdF3-LiF electrolyte as corrosion medium, the temperature of high temperature corrosion is set to 850℃ after measuring the temperature by field temperature gun, and the corrosion time is set to 50 hours. The specific experimental process is as follows: the graphite crucible is fixed on the special crucible support made of 304 stainless steel, a certain amount of electrolyte is poured into the graphite crucible, then the assembled crucible assembly is loaded into the SX13-YBL type box type high temperature resistance furnace, when the electrolyte reaches the molten state, the crucible is taken out and placed in the sample to be tested, then the crucible support is put back into the high temperature resistance furnace, and the timing starts; in order to ensure the continuity of the corrosion process, electrolyte needs to be supplemented every 10 hours during the experiment; after reaching the preset holding time, the crucible is quickly taken out and air cooled, then the graphite crucible is broken, and the sample is taken out; after the experiment, the sample is placed in an ultrasonic cleaner, a hydrochloric acid-hexamethylenetetramine mixed solution is used, then deionized water is used for rinsing, so as to remove the surface residual salt and corrosion products as much as possible, and finally the morphology is characterized.
[0084] Performance characterization and results show that, referring to Figure 1 , the as-cast microstructure of Nb microalloyed low carbon steel after air cooling is uniform ferrite and pearlite. Due to the fine-grained effect of Nb, the austenite grains are not easy to coarsen, which reduces the risk of forming widmanstatten structure, and the microstructure is more uniform during the transformation of austenite to ferrite, and the acicular structure disappears; referring to Figure 2 , during hot working, the gradient temperature deformation reduces the flow stress with the increase of deformation temperature, and the accumulation of strain in each pass leads to the increase of flow stress with the increase of strain in multi-pass deformation, and the resistance of the casting is the largest in the third pass deformation, which is 157.36MPa; referring to Figure 3 , the microstructure of Nb microalloyed low carbon steel after three-pass hot working is martensite; referring to Figure 4 , the original austenite grain size of Nb microalloyed low carbon steel after three-pass hot working is small and uniform, and the average grain size is 23.10μm. This is because the addition of Nb makes the carbide precipitate during hot working, which can effectively inhibit dynamic recrystallization and grain coarsening, and has the effect of fine-grain strengthening and precipitation strengthening; referring to Figure 5 , the surface morphology of Nb microalloyed low carbon steel after three-pass hot working and 50h corrosion under high temperature molten salt condition is relatively uniform, and there is no obvious aggregation or expansion trend; referring to Figure 6 , from the determination of corrosion products after corrosion, the corrosion products after corrosion are composed of F, O and Fe, etc. Under high temperature environment, F - and O 2- form chemical bonds with Fe 2+ and Fe 3+And the Ni, Cr, Mo in the grain boundary region react continuously to generate iron-based / nickel-based / chromium-based / molybdenum-based oxides, fluorides and oxyfluorides, and the periodic peeling of these corrosion products leads to the thinning of the sample thickness, and other components are impurities mixed in the electrolyte.
[0085] Example 2
[0086] 1) The Nb-free low-carbon steel ingot was obtained by smelting and casting according to the raw material ratio shown in Table 2, and the smelting temperature was 1500°C.
[0087] Table 2 Chemical composition of Nb-free low-carbon steel (mass fraction, %)
[0088] C Si Mn S P Ni Cr Nb Fe 0.236 0.266 0.565 0.0023 0.016 0.022 0.022 0 Bal.
[0089] 2) The low-carbon steel was processed into cylindrical samples with a diameter of Φ10mm and a length of 15mm, and then the effect of hot working on the microstructure and properties of the samples was studied.
[0090] 3) The samples were subjected to multi-pass hot compression using a hot compression simulator, and the deformation temperatures selected were 950°C, 1050°C and 1150°C, the strain rate was 1s -1 , and the sample compression mode was consistent with that of Example 1.
[0091] 4) The sample characterization method was consistent with that of Example 1.
[0092] Performance characterization and results show that, please refer to Figure 7 The white area (ferrite) of the as-cast microstructure of the Nb-free low-carbon steel exhibits parallel needle-like or feather-like characteristics (Widmanstatten structure), and during cooling, acicular ferrite or acicular cementite is first precipitated on the austenite grain boundaries, the acicular structure is arranged parallel to the grain boundaries and grows into the grain, and finally presents a feather-like or triangular morphology; please refer to Figure 8 During hot working, the gradient cooling hot deformation reduces the flow stress as the deformation temperature increases, and the accumulation of strain in each pass leads to an increase in the flow stress with increasing strain in multi-pass hot working, and the resistance of the casting is the largest in the third pass deformation, which is 132.38MPa; please refer to Figure 9 The microstructure of the Nb-free low-carbon steel after three-pass hot working is martensite; please refer to Figure 10 The average grain size of the original austenite of the Nb-free low-carbon steel after three-pass hot working is 180μm, which is relatively large; please refer to Figure 11 The surface morphology of the Nb-free low-carbon steel after three-pass hot working and corrosion for 50h under high-temperature molten salt conditions is relatively uneven compared with that of the Nb micro-alloyed low-carbon steel, and there is an obvious trend of aggregation or expansion; please refer to Figure 12 From the determination of the corrosion products after corrosion, it is found that the corrosion products after corrosion are composed of F, O and Fe, and under high-temperature environment, F- With O 2- By chemical bonding with Fe2 + , Fe3 + and Ni, Cr, Mo in grain boundary area, continuously generate iron-based / nickel-based / chromium-based / molybdenum-based oxides, fluorides and fluorine-oxygen complexes, and the periodic peeling of these corrosion products leads to the thinning of the sample thickness, and other components are impurities mixed in the electrolyte.
[0093] Example 3
[0094] 1) According to the raw material ratio shown in Table 3, the steel ingot is obtained by melting, and the melting temperature is 1500℃.
[0095] Table 3 Chemical composition of high-Nb low-carbon steel
[0096] C Si Mn S P Ni Cr Nb Fe 0.241 0.273 0.561 0.0022 0.014 0.024 0.023 0.12 Bal.
[0097] 2) During the melting process of the steel ingot, the corresponding raw materials of each component and niobium-iron alloy are added in sequence to obtain low-carbon steel with high Nb content.
[0098] 3) The Nb-containing low-carbon steel is processed into cylindrical samples with a diameter of Φ10mm and a length of 15mm, and then the effect of hot working on the microstructure and properties is studied.
[0099] 4) The sample is subjected to multi-pass hot compression using a hot compression simulator, and the deformation temperature is selected as 950℃, 1050℃ and 1150℃, and the strain rate is 1s -1 ; The sample compression method is consistent with Example 1.
[0100] 5) The corrosion experiment uses PrNdF3-LiF electrolyte as the corrosion medium, and the temperature of high-temperature corrosion is set to 850℃ after measuring by a temperature measuring gun, and the corrosion time is set to 50 hours. The specific experimental process is as follows: The graphite crucible is fixed on the special crucible support made of 304 stainless steel, a certain amount of electrolyte is poured into the graphite crucible, then the assembled crucible assembly is loaded into the SX13-YBL type box type high temperature resistance furnace, when the electrolyte reaches the molten state, the crucible is taken out and placed in the sample to be tested, then the crucible support is put back into the high temperature resistance furnace, and the timing starts; In order to ensure the continuity of the corrosion process, electrolyte needs to be supplemented every 10 hours during the experiment; After reaching the preset holding time, the crucible is quickly taken out and air-cooled, and the graphite crucible is broken, and the sample is taken out; After the experiment, the sample is placed in an ultrasonic cleaning machine, and a mixed solution of hydrochloric acid and hexamethylene tetramine is used, then deionized water is used for rinsing, and surface residual salt and corrosion products are removed as much as possible, and finally the morphology is characterized.
[0101] Performance characterization and results show that, referring to Figure 13, the as-cast microstructure of high Nb low carbon steel after air cooling is uniform ferrite and pearlite, the austenite grain is not easy to coarsen due to the fine-grain effect of Nb, which reduces the risk of forming widmanstatten structure, and the microstructure is more uniform during the transformation of austenite to ferrite, and the acicular structure disappears; see Figure 14 When hot working, gradient cooling hot deformation makes the flow stress decrease with the increase of deformation temperature, the accumulation of strain in each pass leads to the increase of flow stress with the increase of strain in multi-pass, and the resistance to deformation is the largest in the third pass, which is 140.23 MPa; see Figure 15 The microstructure of high Nb low carbon steel after three-pass hot working is martensite; see Figure 16 The original austenite grain size of high Nb low carbon steel after three-pass hot working is small and uniformly distributed, and the average grain size is 28.10 μm. This is because the high-temperature deformation strength of the trace Nb added casting is improved, and the carbide dispersion precipitation can effectively inhibit dynamic recrystallization and grain coarsening, and has the effect of fine-grain strengthening and precipitation strengthening; see Figure 17 The surface morphology of high Nb low carbon steel after three-pass hot working and corrosion for 50 h under high-temperature molten salt conditions is relatively uneven, the intergranular corrosion is obvious, and there is a tendency of aggregation or expansion; see Figure 18 From the determination of the corrosion products after corrosion, the corrosion products after corrosion are composed of F, O and Fe, etc. Under high-temperature environment, F - and O 2- react with Fe2 + , Fe3 + on the surface of the sample and Ni, Cr, Mo in the grain boundary region respectively through chemical bonding, and continuously generate iron-based / nickel-based / chromium-based / molybdenum-based oxides, fluorides and fluorine-oxygen complexes. The periodic peeling of these corrosion products leads to the thinning of the sample thickness, and other components are impurities mixed in the electrolyte.
[0102] Comparative Example 1
[0103] 1) According to the raw material ratio shown in Table 4, Nb microalloyed low carbon steel ingot was obtained by smelting and casting, and the smelting temperature was 1500℃.
[0104] Table 4 Chemical composition of Nb microalloyed low carbon steel (mass fraction, %)
[0105] C Si Mn S P Ni Cr Nb Fe 0.241 0.273 0.561 0.0022 0.014 0.024 0.023 0.058 Bal.
[0106] 2) The Nb microalloyed low carbon steel was processed into cylindrical samples with a diameter of Φ10 mm and a length of 15 mm, and then the effect of hot working on the microstructure and properties of the samples was studied.
[0107] 3) The sample was subjected to single-pass hot compression by using a hot compression simulator, and the deformation temperature was selected as 950℃, the strain rate was 1s -1The sample compression method is the same as in Example 1.
[0108] 4) The characterization method of the sample is the same as that in Example 1.
[0109] Performance characterization and results are shown in the reference. Figure 20 The average grain size of the original austenite in Nb microalloyed low-carbon steel after a single-pass hot working is 90 μm, which is relatively large; see reference. Figure 21 The surface morphology of Nb microalloyed low-carbon steel after one hot working pass under high-temperature molten salt corrosion for 50 hours is shown. The corrosion morphology is less uniform than that of Nb microalloyed low-carbon steel, exhibiting a clear tendency for aggregation or expansion. (See also...) Figure 22 The analysis of the corrosion products after corrosion revealed that they consisted of substances such as F, O, and Fe. Under high-temperature conditions, F... - With O 2- Through chemical bonding, they respectively interacted with Fe2+ on the sample surface. + Fe3 + The Ni, Cr, and Mo in the grain boundary regions react to continuously generate iron-based / nickel-based / chromium-based / molybdenum-based oxides, fluorides, and fluorine-oxygen complexes. The periodic peeling off of these corrosion products leads to a reduction in sample thickness. Other components are impurities mixed in with the electrolyte.
[0110] In summary, as shown in Examples 1, 2, and 3, gradient cooling hot deformation refines the grain size. However, due to the pinning effect of Nb precipitation relative to grain boundaries, the microstructure after hot deformation is further refined. Therefore, the grain size of the low-carbon steel with added Nb is smaller than that of regular low-carbon steel. Simultaneously, combined with grain orientation, Nb microalloyed low-carbon steel undergoes different gradient cooling hot compressions. Specifically, Nb elements exert a certain degree of resistance to dislocations through pinning or dragging, resulting in superior strength and toughness, thus extending the service life of its application in anode plates of rare earth electrolytic furnaces. The determination of corrosion products after corrosion reveals that they are composed of F, O, and Fe. Under high-temperature conditions, F- and O2- react chemically with Fe2+ on the sample surface. + Fe3 + The corrosion products react with Ni, Cr, and Mo in the grain boundary regions, continuously generating iron-based / nickel-based / chromium-based / molybdenum-based oxides, fluorides, and fluorine-oxygen complexes. The periodic flaking of these corrosion products leads to a reduction in sample thickness. Other components are impurities mixed in with the electrolyte. However, the corrosion resistance of Nb microalloyed steel with a Nb content of 0.058 wt% significantly increases after hot working. This means that the microstructure uniformity can be optimized through multi-pass hot working, which can improve the service stability of low-carbon steel in high-temperature corrosive environments to a certain extent.
[0111] The above examples show that the application provides the Nb microalloy steel with good high-temperature corrosion resistance, and a "stack-rotation-gradient cooling" hot working method and application thereof. The application realizes significant grain refinement by adopting the gradient cooling hot working process and combining with the Nb microalloy design. The gradient cooling process optimizes the phase change process, and the dynamic pinning effect of the Nb(C, N) precipitated phase on the grain boundary further inhibits the grain growth, so that the structure is uniformly refined. The Nb microalloy low-carbon steel treated by the process can control the average grain size of the original austenite to be below 30 microns, which is significantly reduced compared with the traditional process. The synergistic effect of the fine-grain strengthening and the Nb precipitated phase significantly improves the high-temperature oxidation resistance and high-temperature corrosion resistance, and has a significant advantage in the high-temperature corrosion service environment.
[0112] The above only describes the preferred embodiments of the application, and it should be noted that those skilled in the art can make several improvements and refinements without departing from the principles of the application, and these improvements and refinements should also be considered as the protection scope of the application.
Claims
1. A Nb microalloyed steel with good high-temperature corrosion resistance, characterized in that, Includes the following chemical components by mass percentage: C 0.15~0.25%, Si 0.2~0.3%, Mn 0.5~0.6%, Ni 0.02~0.03%, Cr 0.015~0.03%, S≤0.0025%, P≤0.02%, Nb≤0.1% and the balance Fe.
2. The Nb microalloyed steel with good high-temperature corrosion resistance according to claim 1, characterized in that, The mass ratio of C to Nb is 2.5 to 12.
5.
3. The "stack-rotation-gradient cooling" hot working method for Nb microalloyed steel with good high-temperature corrosion resistance as described in claim 1 or 2, characterized in that, Includes the following steps: 1) During the steel ingot smelting process, the corresponding raw materials and niobium-iron alloys are added sequentially to obtain Nb microalloyed steel ingots; 2) After heating the Nb microalloyed steel ingot, it is held at the temperature, then cooled to the temperature of the first hot compression for the first hot compression, and then immediately water quenched. After water quenching, the steel ingot is machined into "strip-shaped" samples of the same size. 3) Heat and hold the Nb microalloyed steel sample obtained in step 2) at the temperature, then cool it down to the temperature of the second hot compression. After holding it at the temperature, rotate it 60° clockwise along the axis of the first hot compression. Take "1 to N" strip-shaped samples with the same cross-sectional size, align the ends and stack them together, then apply axial compression to perform the second hot compression. Where N≤100. 4) After unloading the Nb microalloyed steel sample obtained in step 3), take it out and cool it to the temperature of the third hot compression. After holding it at the temperature, rotate it 60° clockwise along the axis of the second hot compression and then perform the third hot compression. After that, water quenching is performed to obtain Nb microalloyed steel with good high-temperature corrosion resistance.
4. The "stack-rotation-gradient cooling" hot working method for Nb microalloyed steel with good high-temperature corrosion resistance according to claim 3, characterized in that, The steel ingot is smelted at a temperature of 1350–1580°C.
5. The "stack-rotation-gradient cooling" hot working method for Nb microalloyed steel with good high-temperature corrosion resistance according to claim 3 or 4, characterized in that, In step 2), the heating temperature is 1200-1300℃, and the holding time is 150-200s; The cooling rate is 8–12 °C / min, and the first-pass hot compression temperature is 1100–1200 °C.
6. The "stack-rotation-gradient cooling" hot working method for Nb microalloyed steel with good high-temperature corrosion resistance according to claim 5, characterized in that, In step 3), the Nb microalloyed steel ingot is heated to 1250°C and held for 180 seconds. The second hot compression temperature is 1000–1100℃, the cooling rate is 8–12℃ / min, and the holding time is 100–150s.
7. The "stack-rotation-gradient cooling" hot working method for Nb microalloyed steel with good high-temperature corrosion resistance according to claim 3, 4, or 6, characterized in that, In step 4), the temperature of the third hot compression is 900-1000℃, the cooling rate is 8-12℃ / min, and the holding time is 100-150s.
8. The "stack-rotation-gradient cooling" hot working method for Nb microalloyed steel with good high-temperature corrosion resistance according to claim 7, characterized in that, The reduction rates of the first, second, and third hot compression passes are independently 15-30%, the total deformation rate of the hot compression is ≥60%, and the strain rate of the hot compression is 1s for each pass. -1 The engineering strain is 0.
2.
9. The application of the high-temperature corrosion-resistant Nb microalloyed steel as described in claim 1 or 2 in the structural metallic materials of anode pressure plates, stirring rods, and molten salt heating furnaces for rare earth electrolysis furnaces.